Edukasi Kesehatan Jiwa Keluarga di Masyarakat Kenagarian Sungai Tanang Kecamatan Banuhampu, Sumatera Barat - Novia Zulfa Hanum; Nurmaines Adhyka; Intan Kamala Aisyiah; Tosi Rahmaddian; Amrizal Arief (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
This service program aims to increase understanding and support for mental health in rural communities, especially in Kenagarian Sungai Tanang, West Sumatra. The main problems faced are lack of access to mental health services, stigma towards mental health problems, and lack of understanding of the importance of mental health at the family level. The aim of this activity is to increase public understanding about mental health, strengthen the role of families in providing support to family members who need it, and increase access to mental health services. The methods used include developing educational materials, implementing interactive workshops, mentoring, and program evaluation. The results of this activity show an increase in public understanding about mental health, an increase in the active role of families in providing support, expansion of access to mental health services, and a reduction in stigma towards mental health problems. This program makes a positive contribution in improving the mental health welfare of the Kenagarian Sungai Tanang rural community and provides direction for the development of similar programs in other rural areas.